2020
DOI: 10.1002/ajp.23175
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular shape variation in mainland and insular hylobatids

Abstract: Although hylobatids are the most speciose of the living apes, their morphological interspecies and intraspecies variation remains poorly understood. Here, we assess mandibular shape variation in two species of Hylobates, white‐handed (Hylobates lar) and black‐handed (Hylobates agilis) gibbons. Using 71 three‐dimensional landmarks to quantify mandibular shape, interspecies and intraspecies variation and geographic patterns of mandibular shape are examined in a mixed sex sample of adult H. lar and H. agilis thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 104 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…The shape of the extant catarrhines corpus is a useful taxonomic discriminator and has been implicated in taxonomic discrimination among extant cercopithecoids (Takahashi and Pan, 1994; Jablonski et al, 1998; Daegling and McGraw, 2001; Pan et al, 2002, 2008; Wright et al, 2008) and hominoids (Daegling, 1989; Humphrey et al, 1999; Taylor, 2002; Taylor and Groves, 2003; Taylor, 2006a; Pitirri and Begun, 2019; Pitirri et al, 2020). The sources of variation in corpus shape, notably sexual dimorphism and ontogeny, were clarified in extant hominoids (Wood et al, 1991; Daegling, 1996; Brown, 1997; Taylor, 2006b; Singh, 2014; Pitirri and Begun, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the extant catarrhines corpus is a useful taxonomic discriminator and has been implicated in taxonomic discrimination among extant cercopithecoids (Takahashi and Pan, 1994; Jablonski et al, 1998; Daegling and McGraw, 2001; Pan et al, 2002, 2008; Wright et al, 2008) and hominoids (Daegling, 1989; Humphrey et al, 1999; Taylor, 2002; Taylor and Groves, 2003; Taylor, 2006a; Pitirri and Begun, 2019; Pitirri et al, 2020). The sources of variation in corpus shape, notably sexual dimorphism and ontogeny, were clarified in extant hominoids (Wood et al, 1991; Daegling, 1996; Brown, 1997; Taylor, 2006b; Singh, 2014; Pitirri and Begun, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Across anthropoid primates, several geographically widespread clades exhibit patterns of morphological covariation with geographic and environmental parameters (e.g., Cáceres et al, 2014; Cardini et al, 2007; Cardini & Elton, 2009; Fooden & Albrecht, 1993; Frost et al, 2003; Groves, 1970; Grunstra et al, 2018; Harvati & Weaver, 2006; Jabbour & Pearman, 2016; Meloro, Cáceres, Carotenuto, Passaro, et al, 2014; Pitirri et al, 2020; Turner et al, 1997, 2018; Weinstein, 2011). In particular, latitudinal patterns in body size and relative limb lengths reflecting Bergmann's and Allen's rules respectively have been observed in many mammalian taxa, including primates (e.g., Albrecht & Miller, 1993; Ashton et al, 2000; Harcourt & Schreier, 2009; Meiri & Dayan, 2003; Turner et al, 2018; Weinstein, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Factors threatening primates are dynamic and interact with each other at local, regional, and national scales, leading to a reduction in population sizes and, a probable extinction (Estrada et al, 2017). Previous studies have shown that morphology covaries with ecological parameters in Malagasy primates (e.g., Andrews et al, 2020;Meloro et al, 2015;Pitirri et al, 2020;Pitirri & Begun, 2019;Raveloson et al, 2005;Ravosa, 1990Ravosa, , 1991Ravosa, , 1992Ross et al, 2012) but also that the morphofunctional adaptations are difficult to discern from other sources of mandibular variation (e.g., Humphrey et al, 1999;Marcé-Nogué et al, 2017;Meloro et al, 2015;Pitirri et al, 2020;Raveloson et al, 2005;Ravosa, 1990;Ross et al, 2012;Schmittbuhl et al, 2007;Taylor & Groves, 2003). In addition, morphology clearly carries a phylogenetic signal (Fleagle et al, 2010(Fleagle et al, , 2016Masters et al, 2014;Masters & Couette, 2015;St Clair & Boyer, 2016).…”
mentioning
confidence: 99%